Advances in hydrogeology - Kuhlman, Kristopher L.; Mishra, Phoolendra K. (Springer New York, 2013)
This book brings together different types of advances in hydrogeology, including mathematical and numerical conceptualization changes, different approaches to simulating groundwater flow and transport, and both field and laboratory hydrogeologic characterization advances. Each chapter extends or summarizes a recent development in hydrogeology, with forward-looking statements regarding both the strengths and limitations of each new advances.